Hydrogenation of Lignin‐derived Phenolic Compounds over Ru/C Enhanced by Al2O3 Catalyst at Room Temperature. Issue 19 (18th May 2022) - You, Hongyun; Yang, Zhi; Lin, Jingjun; Shu, Riyang; Yin, Tao; Tian, Zhipeng; Wang, Chao; Chen, Ying
Abstract: Hydrogenation is a promising strategy for the lignin‐derived phenolic compounds to produce platform chemical compounds and high‐value biofuel precursors. In this study, an efficient hydrogenation of phenol over Ru/C enhanced by Al2 O3 catalyst at room temperature was proposed, with phenol conversion and cyclohexanol selectivity both close to 100 %. The addition of Al2 O3 can make a significant difference on the phenol adsorption by the introduction of abundant Lewis acid site, which enabled to activate aromatic rings by changing the electrophilic substitution reaction of aromatic groups and trigger the occurrence of phenol hydrogenation under the catalysis of Ru/C. The Lewis acid site and metal site cooperated with each other and promoted the conversion of phenol to cyclohexanol as the final products. Moreover, a variety of other phenolic or aromatic compounds were also tested. The steric effects derived from the different substituted groups on aromatic rings had a significant influence on the hydrogenation performances. Abstract : This paper proposed an efficient hydrogenation of phenol over Ru/C enhanced by Al2 O3 catalyst at room temperature, with phenol conversion and cyclohexanol selectivity both close to 100 %. The addition of Al2 O3 can make a significant difference on the phenol adsorption by the introduction of abundant Lewis acid site, which enabled to activate aromatic rings by changing the electrophilic substitution reaction of aromatic groups and trigger the occurrence of phenol hydrogenation under the catalysis of Ru/C.